APPLIANCE OF SCENARIO PLANNING METHOD FOR RUSSIAN AIRLINES ACTIVITY - G. V. Kreneva (Научный вестник МГТУ ГА, 2016)
The article examines scenario planning as a tool for long-term forecasting of airlines activity in an uncertainty. This method is compared to linear programming (linear scheduling method) with their advantages and disadvantages being discussed. Scenario analysis is shown as a main tool in scenario-based forecasting. The scheme of scenario development is performed. Scenario planning experience in European airlines is considered. Uncertainty factors faced by Russian airlines are analysed. In the conclusion the author proposes to apply scenario planning widely as it will be useful for long-term planning in Russian airlines and will sustain their competitiveness and efficiency.